2010
DOI: 10.1002/pola.24143
|View full text |Cite
|
Sign up to set email alerts
|

Well‐controlled amphiphilic block glycopolymers and their molecular recognition with lectins

Abstract: The atom transfer radical polymerization of an unprotected glycomonomer, 2‐{[(D‐glucosamin‐2N‐yl)carbonyl]oxy}ethyl methacrylate (HEMAGl) is firstly reported. Controlled polymerizations were performed with the CuBr/N,N,N′,N′,N′‐pentamethyldiethylene triamine catalytic system with ethyl 2‐bromoisobutyrate and 1,2‐bis(bromoisobutyryloxy) ethane as mono and difunctional initiators in DMF solutions (80% w/w) at 40 and 50 °C, respectively. The polymerization of HEMAGl resulted in a controlled polymerization with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…The synthesis of 2‐{[( D ‐glucosamin‐2‐ N ‐yl)carbonyl]oxy}ethyl methacrylate, HEMAGl, is described elsewhere 26. Methyl acrylate, MA (Merck), was purified by a conventional method 32.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of 2‐{[( D ‐glucosamin‐2‐ N ‐yl)carbonyl]oxy}ethyl methacrylate, HEMAGl, is described elsewhere 26. Methyl acrylate, MA (Merck), was purified by a conventional method 32.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the considerable progress in glycopolymers synthesis, most synthetic methods require the protection of carbohydrate hydroxyl groups and several purification pathways. Recently, we reported the synthesis of a novel unprotected glycomonomer based on glucosamine and their polymerization via controlled radical polymerization 26…”
Section: Introductionmentioning
confidence: 99%
“…The di-and triblock copolymers containing HEA units were initially activated with p-nitrophenyl carbonate groups and the degree of modification 50 nm was estimated by NMR. Figure 5 shows the 1 H and 13 C-NMR spectra of the diblock PBA 64 Table 2. These degrees are lower than those obtained with HEMA copolymers.…”
Section: Preparation and Characterization Of Amphiphilic Block Glycopmentioning
confidence: 99%
“…The binding behavior of these amphiphilic glycopolymers was then compared with that found for PHEAnGl homopolymer at similar degree of modification (degree of polymerization of 132 monomer units and 28 wt% of glucosamine units). Presence of the PBA hydrophobic block favors the binding process as a result of hydrophobic interactions,[29,54,64,65] as deduced from the comparison of the results obtained for the PHEAnGl homopolymer with those determined for the di and triblock glycopolymers, all of them being also represented inFigure 9. This is a consequence of the arrangement of block copolymers to form micelar structures with high amount of saccharide groups at the surface, in concordance with the data obtained by DLS.…”
mentioning
confidence: 91%
“…Leon et al [138,139] reported the synthesis of amphiphilic block glycopolymers derived from D-glucosamide methacrylate M63. According to one strategy (Entry 121-124, Table 2), M63 was homopolymerized using a monofunctional (A1) or a bifunctional initiator (A27) at 40 and 50 °C respectively (DMF, CuBr(L3)).…”
Section: (Meth)acrylate Monomersmentioning
confidence: 99%